Designing a circular business strategy: 7 years of evolution at a large washing machine manufacturer. (5th November 2021) - van Loon, Patricia; Van Wassenhove, Luk N.; Mihelic, Ales
Abstract: This paper discusses the development of circular business models for a large white goods manufacturer. A 7‐year journey in designing, discussing, adapting, and finally finding a potentially profitable circular offer is summarized, and the barriers that had to be overcome in this process are highlighted. The shift from selling washing machines to repeated leases with remanufacturing steps in‐between turned out to be very challenging. Despite the numerous claims in the consulting world that both manufacturers and consumers can benefit from the transition to a circular economy, it took multiple iterations to find a business model with the potential of being economically attractive to both the company and the client. The transformation process of shifting to a circular business model tends to be highly underestimated by companies and involves many issues beyond product design such as customer relationships, return logistics, remanufacturing operations, and service contracts. Researchers will need to work with companies to address the transition issues and to increase the relevance of circular economy research.